Association of Codon 72 Polymorphism in Exon 4 of the TP53 Gene in Benign and Malignant Breast Tumors in Senegal - Samb, Hijeux Minte Cheikh Mohamed Malainy; Ndong, Anna; Sembene, Mbacké (European Journal of Applied Sciences, 2026)
Background: The Arg72Pro (R72P) polymorphism of the TP53 tumor suppressor gene has been controversially associated with breast cancer risk, with significant variations depending on ethnic origin. Little data exists for West African populations. This study seeks to evaluate the distribution and association of the R72P polymorphism of exon 4 of the TP53 gene with benign and malignant breast tumors in the Senegalese population. Methodology: The study was conducted on 48 Senegalese women: 17 with breast cancer (malignant), 12 with benign tumors, and 19 healthy controls. The polymorphism was genotyped by PCR followed by restriction fragment analysis. Polymorphism and allelic diversity, as well as genetic differentiation parameters and correspondence factor analysis, were generated using Genetix software version 4.05.2 and Bayesian inference with STRUCTURE. Hardy-Weinberg equilibrium was tested using GenePop software version 4.3. Results: The analysis revealed a distinct allele distribution, with a predominant frequency of the C allele (Pro72) in controls (77.7%) and an increased frequency of the G allele (Arg72) in patients with tumors (25% malignant, 12.5% benign). Statistically, no significant association was found between genotypes and the risk of developing malignant or benign breast tumors. Hardy-Weinberg equilibrium tests showed a significant imbalance in the patient populations, unlike in the controls. Finally, population genetic analyses (low FST differentiation indices, negligible genetic distances, and genetic structure in two clusters) indicated high genetic homogeneity between the three groups for this specific locus. Conclusion: Although differences in allele frequency were observed, the R72P polymorphism of TP53 is not an independent and significant risk factor for breast cancer in this Senegalese cohort. The high genetic homogeneity observed suggests that this variant alone is probably not a key determinant of breast pathology in this population. These results highlight the importance of local studies and the need for broader research incorporating other genetic and environmental factors.